RESISTANCE TO NEWER BETA-LACTAMS AND RELATED ESBL TYPES IN GRAM-NEGATIVE NOSOCOMIAL ISOLATES IN TURKISH HOSPITALS: RESULTS OF THE MULTICENTRE HITIT STUDY - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2008)
Increasing resistance due to extended-spectrum beta-lactamases (ESBLs) and multiple resistance mechanisms in gram-negative hospital isolates restrict the role of R-lactam antibiotics in empirical treatment of serious infections. As the prevalence of ESBL producing strains and resistance rates to antimicrobial agents can vary in each center, local surveillance studies are required to guide therapy. In this study, in vitro rates of resistance to ceftriaxone, ceftazidime, cefepime, imipenem, cefoperazone/sulbactam and piperacillin/tazobactam were evaluated in 1196 gram-negative hospital isolates in a multicenter in vitro study with the participation of six different centers in Turkey between the period of June 2004-January 2005. The isolates included Escherichia coli (n= 457), Klebsiella pneumoniae (n= 390), Pseudomonas aeruginosa (n= 194) and Acinetobacter baumannii (n= 155). In addition, frequency of ESBL production and types of enzymes were determined in blood isolates of E.coli and K.pneumoniae. MICs and ESBL production were investigated by E-test (AB Biodisk, Solna) and the results were evaluated by using CLSI breakpoints. PCR analysis was used for typing of the ESBLs. In E.coli, 26% and in K.pneumoniae 32% of the isolates were ESBL producers. Among the blood isolates of E.coli and K.pneumoniae, 31.7% and 33.3% produced ESBLs, respectively. CTX-M (71.4%) was the most prevalent enzyme, followed by TEM (49.4%) and SHV (46,7%) derived enzymes. CTX-M-15 (69.4%) was the most frequent CTX-M type in blood isolates followed by CTX-M-3 (28.6%) and CTX-M-1 (2%). Resistance to imipenem was not observed in E.coli isolates, however it was 1.3% in K.pneumoniae, 28.9% in P.aeruginosa and 52.2% in A.baumannii strains. Resistance to cefoperazone/sulbactam was found as 6%, 17.7%, 27.9% and 41.3% in E.coli, K.pneumoniae, P.aeruginosa and A.baumannii isolates, respectively, whereas resistance rates to piperacillin/tazobactam were 10.2%, 22.3%, 22.7% and 78.7%, respectively. These results indicate that ESBL production and rates of resistance to R-lactam antibiotics are high in hospital isolates of gram-negative bacteria in Turkey, however, they show variations in different hospitals and CTX-M enzymes are prevalent in these isolates.
Keywords: Antimicrobiol resistance; extended-spectrum beta-lactamase; gram-negative bacteria; CTX-M; beta-lactamase inhibitor; KLEBSIELLA-PNEUMONIAE; CTX-M; ESCHERICHIA-COLI; CLINICAL ISOLATE; TURKEY; INFECTIONS; CTX-M-15; KOREA